Immunohistochemical and Morphological Features of Bovine Granulosa Cell Tumours in Relation to Growth Pattern and Folliculogenesis. (August 2021) - Teh, Angeline P.P.; Kitahara, Go; Izzati, Uda Z.; Mori, Keita; Fuke, Naoyuki; Hirai, Takuya; Yamaguchi, Ryoji
Summary: Granulosa cell tumours (GCTs) are the most common type of bovine ovarian neoplasm. We describe the morphological and immunohistochemical features of GCTs (n = 26) and a thecoma (n = 1) using antibodies to cytokeratin AE1/AE3, vimentin, desmin, nectin-4, anti-Müllerian hormone (AMH), inhibin α, c-erbB-2 oncoprotein and proliferating cell nuclear antigen. The results indicate that, based on the expression similarity of AE1/AE3 and inhibin α, the macrofollicular growth pattern of GCTs derives from highly differentiated granulosa cells (GCs), the Graafian follicle or early atretic follicle. The trabecular growth pattern of GCTs is inferred to be derived from GCs of the atretic follicle in mature animals. AMH is a useful marker for diagnosing bovine sex cord-stromal tumours because it was expressed in all GCT cases and in the single case of thecoma.